Optimization and economic evaluation of integrated natural gas liquids (NGL) and liquefied natural gas (LNG) processing for lean feed gas. (25th February 2019) - Jin, Chunhe; Lim, Youngsub
Graphical abstract: Highlights: Process efficiency and economic performance were investigated for the integrated processes. The proposed case 1 process has economic advantages compared to the base case scheme. Case 2 process shows the best profitability when the operation time was short. Abstract: There is an increasing demand for economic evaluation of integrated liquefaction and natural gas liquids (NGL) recovery processes for lean feed. This paper performs economic analysis for the conventional liquefied natural gas (LNG) and NGL coproduction process compared to two proposed simple integrated processes considering the LNG higher heating value (HHV) specification under lean feed conditions. Dual mixed refrigerant (DMR) cycle was used for liquefaction in the conventional and one of the proposed processes. Single mixed refrigerant (SMR) cycle was selected for the other simplified proposed process, which has the advantage of lowering capital expenditure compared with the DMR cycle. The process schemes were built by the commercial software Aspen HYSYS, and a genetic algorithm (GA) was used for process optimization. The results show that the first proposed integrated process has economic advantages compared to the conventional scheme under the lean feed composition (which represents different results from previous studies reported under conventional feed conditions). Additionally, capital cost was reduced remarkably by simplifying the NGL recovery section with little loss of liquefaction efficiency. The second proposed process has the lowest capital expenditure and shows best profitability for plants operating for less than 15 months, but the liquefaction efficiency is lower than the other two schemes.